PENGARUH MOTIVASI, DISIPLIN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Sudi Pada Kantor PT. Kereta Api Indonesia DAOP IV Kota Semarang) - Siti Kunderi, 14.05.51.0224; Suhatmanto, Toto (Students' Journal of Economic and Management, 2018)
This study analyzed the effect of motivation, work discipline, and compensation on employee performance. Object of study in this paper is the PT. Kereta Api Indonesia DAOP IV Semarang City. The sampling technique in this research is to use simple random sampling (random) sample of 60 respondents as data collection method using a questionnaire (questionnaire) by distributing a list of questions to the respondent in order to obtain information. The data were analyzed using factor analysis to test the validity of the question item, cronbach alpha formula to test the reliability of each of the independent variables were tested by regression analysis. The result showed that the motivation has a positive effect and significant to the employee performance, work discipline has a positive effect and significant to the employee performance, and compensation has a positive effect and significant to the employee performance.Keyword : motivation, work discipline, compensation, and employee performance